2012
DOI: 10.1017/s0007114511006246
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D supplementation during pregnancy on neonatal mineral homeostasis and anthropometry of the newborn and infant

Abstract: Hypovitaminosis D is common in India. In the present prospective partially randomised study of vitamin D (D 3 ) supplementation during pregnancy, subjects were randomised in the second trimester to receive either one oral dose of 1500 mg vitamin D 3 (group 1, n 48) or two doses of 3000 mg vitamin D 3 each in the second and third trimesters (group 2, n 49). Maternal 25-hydroxyvitamin D (25(OH)D) at term, cord blood (CB) alkaline phosphatase (ALP), neonatal serum Ca and anthropometry were measured in these subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
2
19

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(121 citation statements)
references
References 28 publications
2
98
2
19
Order By: Relevance
“…Postnatally the infants continued in their treatment arms by receiving placebo, 400 IU, or 800 IU of vitamin D daily. 25-Hydroxyvitamin D rose faster in the high-dose group, but by 6 mo of age the values were no different among the three groups of infants (78,85, and 84 nM, respectively), and there was no difference in serum calcium at any postnatal time point (233 (294). Small increments in length, head circumference, and weight, and a slight decrease in anterior fonatelle length, were seen in the both vitamin D groups compared with the nonrandomized controls (294).…”
Section: Interventional Studiesmentioning
confidence: 84%
“…Postnatally the infants continued in their treatment arms by receiving placebo, 400 IU, or 800 IU of vitamin D daily. 25-Hydroxyvitamin D rose faster in the high-dose group, but by 6 mo of age the values were no different among the three groups of infants (78,85, and 84 nM, respectively), and there was no difference in serum calcium at any postnatal time point (233 (294). Small increments in length, head circumference, and weight, and a slight decrease in anterior fonatelle length, were seen in the both vitamin D groups compared with the nonrandomized controls (294).…”
Section: Interventional Studiesmentioning
confidence: 84%
“…There was no effect on mode of delivery, C-section rates, adverse events, live versus stillbirths, or gestational age at delivery. (455). There were no differences in obstetrical outcomes, including gestational age at delivery, intrauterine death, pregnancy-induced hypertension, cephalopelvic disproportion, nonprogression of labor, cesarean section, and placenta previa (455).…”
Section: Yu Etmentioning
confidence: 94%
“…But maternal overweight/obesity also causes low 25OHD by binding the fat-soluble vitamin D into the maternal fat stores, and by additional associations with reduced vitamin D intake, less time spent outdoors, etc. Consequently, the studies reporting associations between vitamin D intake or 25OHD levels and obstetrical outcomes may really be demonstrating residual confounding from the link between obesity and these outcomes, and also need to consider that the results of the existing randomized trials did not find these outcomes in their primary analyses (183,184,367,399,455,710,779,966,1013). Larger randomized trials that compare truly vitamin D-deficient to sufficient mothers are needed to properly test the hypothesis, and eliminate the confounding caused by maternal overweight and obesity.…”
Section: Yu Etmentioning
confidence: 99%
“…We found that vitamin D supplementation in pregnant women with GDM resulted in decreased newborn's hyperbilirubinemia. Improved liver enzyme levels in cord blood (CB) of the infants whose mothers received one dose of 1 500 μg vitamin D3 in the second trimester or 2 doses of 3 000 μg vitamin D3 each in the second and third trimesters were seen compared with the controls [18]. In another study by Marya et al [33] supplementation with 2 large doses of 600 000 IU each in the 7 th and 8 th months has led to a significant improvement in serum liver enzyme in [17,34].…”
mentioning
confidence: 99%